Indonesian islamic bank return on assets analysis: Moderating effect of musyarakah financing - Rafidah, Rafidah (al-Uqud : Journal of Islamic Economics, 2023)
This study aims to determine the effect of third-party funds, non-performing financing, and financing on the deposit ratio of ROA using musyarakah financing as an intervening variable. The method used was path analysis with financial statements of Islamic banks in Indonesia for five years, from 2016 to 2021. The results show that third-party funds and financing on the deposit ratio positively and significantly affect musyarakah financing. Non-performing financing has a positive, but insignificant, effect. Third-party funds and musyarakah financing have a positive and significant effect on return on assets, and non-performing financing and financing on the deposit ratio are negative and significant. Additional findings from this study indirectly indicate that third-party funds, non-performing financing, and financing on deposit ratio through musyarakah financing are not significant for return on assets. Musyarakah financing is not an intervening variable that can indirectly affect ROA. Therefore, Islamic banks must increase third-party funds, financing on deposit ratios, and musharaka financing, and reduce non-performing financing. Based on this research, Islamic banks should continue to increase third-party funds, increase musyarakah financing from existing funds, and maintain non-performing financing for musyarakah financing so that financing problems do not occur. Third-party funds obtained from customers should also be allocated to other financing sources, such as mudharabah and murabahah, as well as investments elsewhere.